Diseño de un programa de responsabilidad social empresarial para la distribuidora de medicamentos farmacéuticos José Verdezoto Cía. Ltda. de la ciudad de Cuenca, año 2014. - Montaño Samaniego, Diego José (2014)
Corporate Social responsibility today is a modern way of doing business in a sustainable way, this sustainably covers issues related to accountability to its different groups of interest or stakeholders (shareholders, employees, customers, suppliers, community, environment, State)economic, social and environmental. This investigative work makes reference to the "design of a program of Corporate Social responsibility for the distributorship of pharmaceutical drugs José Verdezoto Cía Ltda.., of the city of Cuenca, year 2014", and will provide economic, environmental and social information of the Distributor to its different stakeholders. The design of the program of Corporate Social responsibility (sustainability report) to the distributor of drugs pharmaceutical José Verdezoto will contribute to the company to engage fully with their stakeholders and to answer for their actions, this will benefit it to be an exemplary Distributor and many other distributors of drugs begin to imitate this great management innovative and interesting for the community